Cobalt Corroles with Bis‐Ammonia or Mono‐DMSO Axial Ligands. Electrochemical, Spectroscopic Characterizations and Ligand Binding Properties. Issue 38 (1st October 2018) - Quesneau, Valentin; Shan, Wenqian; Desbois, Nicolas; Brandès, Stéphane; Rousselin, Yoann; Vanotti, Meddy; Blondeau‐Patissier, Virginie; Naitana, Mario; Fleurat‐Lessard, Paul; Van Caemelbecke, Eric; Kadish, Karl M.; Gros, Claude P.
Abstract : Four bis‐ammonia ligated cobalt corroles and four mono‐DMSO ligated cobalt corroles with different meso ‐aryl substituents on the macrocycle (A2 B‐ and A3 ‐corroles) were synthesized and investigated as to their electrochemical and spectroscopic properties under different solution conditions. The complexation energies of the investigated cobalt corroles were theoretically calculated to illustrate the propensity of the cobalt center for penta‐coordination or hexa‐coordination with various axial ligands (DMSO, CO, py and NH3 ). The structure of one hexacoordinate bis‐NH3 cobalt corrole complex was also determined by X‐ray diffraction. Abstract : Four bis‐ammonia ligated cobalt corroles and four mono‐DMSO ligated cobalt corroles with different meso ‐aryl substituents on the macrocycle (A2 B‐ and A3 ‐corroles) were synthesized and investigated as to their electrochemical and spectroscopic properties under different solution conditions.